Rice Kefiran Ameliorates Obesity and Hepatic Steatosis Through the Change in Gut Microbiota - Takuto Kurakawa; Koudai Kani; Seita Chudan; Miyu Nishikawa; Yoshiaki Tabuchi; Kazuichi Sakamoto; Yoshinori Nagai; Shinichi Ikushiro; Yukihiro Furusawa (Microorganisms)
Obesity is a global epidemic and a significant risk factor for various diseases. Obesity and dysbiosis are associated, drawing attention to the mechanisms that regulate the gut microbiota. In this study, we focused on the postbiotic effects of rice kefiran (Kef), a functional product of Lactobacillus kefiranofaciens cultured in a rice-based medium, on obesity and its complications. Although Kef has the potential to improve obesity, the underlying mechanisms remain unknown. Therefore, we aimed to elucidate the mechanisms underlying changes in gut microbiota. The administration of Kef significantly suppressed diet-induced body weight gain, reduced liver fat accumulation, and modestly improved insulin resistance. Among the gut bacteria, Lachnospiraceae and Lachnoclostridium, which were positively correlated with obesity, decreased in mice administered Kef. In contrast, Bacteroides and Alistipes, both reported to ameliorate obesity, were increased. Consistent with the changes in the gut microbiota, Kef increased fecal acetate levels, which ameliorated obesity and hepatic steatosis. Predictive metagenomic analysis suggested that Kef administration increased the abundance of KEGG orthologs, associated with carbohydrate metabolism and improvements in insulin resistance. In conclusion, Kef improves diet-induced obesity, hepatic steatosis, and insulin resistance by regulating the gut microbiota’s composition.